Comparative Effects of Sodium Bicarbonate and Intravenous Lipid Emulsions on Reversing Bupivacaine-Induced Electrophysiological Toxicity in a Porcine Experimental Model. (July 2019) - Zaballos, Matilde; Callejo, David; Sevilla, Raul; Quintela, Oscar; López-Menchaca, Ramiro; Melone, Arturo; Varela, Olalla; Anadón Baselga, Mª José; Almendral, Jesús
Abstract : BACKGROUND: Bupivacaine cardiotoxicity mainly manifests as inhibition of the cardiac sodium channel, which slows conduction, particularly at the ventricular level. Experimental studies have demonstrated that intravenous lipid emulsions (ILEs) can reduce the cardiotoxic effects of bupivacaine, but the extent of these effects is controversial. Sodium bicarbonate (B) represents the standard treatment of toxicity related to sodium channel–blocking drugs. The aim of this study was to compare the effects of ILEs and B on the speed of recovery from bupivacaine-induced effects on the electrocardiographic parameters. METHODS: Bupivacaine 4 mg/kg was administered to 24 anesthetized pigs. Three minutes after delivering the bupivacaine bolus, the animals were given the following: ILE 1.5 mL/kg followed by 0.25 mL/kg/min (ILE group) and B 2 mEq/kg followed by 1 mEq/kg/h (B group). Controls (C group) were given saline solution, 50 mL followed by 1 mL/kg/h. Electrophysiological parameters were evaluated in sinus rhythm and during right ventricular pacing at several time intervals up to 30 minutes. Data were analyzed as the area under the curve (AUC) for the first 10 minutes (AUC10 ) or 30 minutes (AUC30 ). RESULTS: Bupivacaine increased the sinus cycle length, PR interval, and QRS duration. AUC30 of the sinus rhythm QRS duration after antidote administration was significantly different among the 3 groups ( P = .003). B group experienced faster recovery from intoxication than the C group (AUC10, P = .003; AUC30, P = .003) or the ILE group (AUC10, P = .018). During the first minute, 50% of the B group (versus 0% of the ILE and C groups) had recovered >30% of QRS duration ( P = .011). The trend toward faster recovery in the ILE group than in the C group did not reach significance (AUC10, P = .23; AUC30, P = .06). Effects on the paced QRS duration at a rate of 150 bpm were more intense but with similar results (B versus C group: AUC10, P = .009; AUC30, P = .009; B versus ILE: AUC10, P = .015; AUC30, P = .024). The recovery process of the paced QRS tended to be slower for all antidotes. CONCLUSIONS: In a closed-chest swine model, B was an effective treatment for electrophysiological alterations caused by established bupivacaine toxicity. At clinical doses, B ameliorated bupivacaine electrocardiographic toxicity faster than ILE. Use-dependent effects of bupivacaine are prominent and delay the effects of both antidotes, but B produces faster recovery than ILE.